“AI et al.” The perils of overreliance on Artificial Intelligence by authors in scientific research - Juan S. Izquierdo-Condoy; Jorge Vásconez-González; Esteban Ortiz-Prado (Clinical eHealth)
The rapid integration of Artificial Intelligence (AI) into scientific research and publication processes marks a significant shift in knowledge generation. This transition from traditional literature searches to AI-driven algorithms has accelerated tasks such as writing, editing, and summarizing scientific manuscripts. While AI holds promise for improving efficiency and accuracy, concerns have arisen about its potential misuse and the erosion of scientific integrity.